PENINGKATAN KEMAMPUAN NUMBER SENSE SISWA MELALUI MEDIA PEMBELAJARAN MATEMATIKA BERBANTUAN SOFTWARE LECTORA INSPIRE - Frida Marta Argareta Simorangkir; Ribka Kariani Br Sembiring (MES: Journal of Mathematics Education and Science, 2018)
Abstract. The objectives of this study were (1) to describe the use of mathematics learning media assisted by the Lectora Inspire software to improve the number sense ability of students, (2) to describe the increase in the ability of students' number sense through mathematics learning media assisted by Lectora Inspire software. The ability of the number sense studied is related to ordinary fractional material. Indicator of the number sense ability in question is understanding the basic meaning of fractions, understanding the effect of operations on fractions and using appropriate calculations. This study is a classroom action research, carried out at SD Swasta Kartika I-2 Medan in the academic year 2018/2019. Based on the results of the study showed that the mathematics learning media assisted by the Lectora Inspire software in the developed class V SD fraction material was declared feasible to use because it could affect the students' number sense ability. Based on the results of the final test in cycle I, there were 15 students (41.67%) achieving KKM scores, while the final test results in cycle II obtained 31 students (86.11%) achieved the KKM score. Based on the results of the end of cycle I and II tests obtained as many as 16 students (44.44%) experienced an increase in the number sense ability related to fraction material. The results of the observation sheet for teacher and student activities in the first and second cycles are in good category. Thus it can be stated that there is an increase in the number sense ability of students through mathematics learning media assisted by the Lectora Inspire software.Keywords: Number Sense, Mathematics Learning Media, Lectora Inspire Software